IMPLEMENTASI PENGALOKASIAN DANA DESA DI DESA DUNDANGAN KECAMATAN PANGKALAN KURAS TAHUN 2018 - Masitoh Nursapuri; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Village Funds are funds sourced from the State Revenue and Expenditure Budget used for Villages which are transferred through the Regency/City Regional Revenue and Expenditure Budget and used for government administration, implementation, development, and community empowerment. The purpose of this study is to find out and analyze how the Implementation of Village Fund Allocation in Dundangan Village, Pangkalan Kuras District, and the factors that hinder it. The theory used is the theory of program implementation by Charles O. Jones, there are three indicators that affect implementation: organization, interpretation, and application. This study uses a qualitative research type with a phenomenological approach and the data needed both primary and secondary were obtained through the interviews, observation, and documentation techniques for further data analysis using descriptive data analysis techniques. The results of this study indicate that, first, the implementation of the Village Fund Allocation has not been optimal in terms of organizational structure, implementing programs, coordination, activity schedules, and performance. Second, the factors that hinder the Implementation of Village Fund Allocation in the Dundangan Village, Pangkalan Kuras District, are human resources, coordination, communication, and span of control factors. Keywords: Village Fund, Implementation, Allocation